Research on the Construction of Youth Network Literacy from the Perspective of Cyber Space Security - Zhang, Yexin (Education Insights, 2026)
As the "fifth domain" of jurisdictional integrity, cyberspace has emerged as an indispensable frontier within the comprehensive framework for public safety and systemic social stability. Within this landscape, youth groups, as "digital natives" and the most active participants in the online ecosystem, possess a level of network literacy that is directly tied to the resilience of digital environment protection and the sustainable advancement of the strategic vision for a robust digital state. However, the rapid evolution of technologies—such as Generative AI, algorithmic recommendation engines, and deepfakes—has introduced unprecedented complexity into the online environment, creating new challenges for social order and individual development. This research, grounded in the strategic perspective of network safety, systematically evaluates the multidimensional impacts of the current network ecology on the cognitive frameworks, behavioral norms, and value systems of young individuals. The study identifies critical structural deficiencies in contemporary youth network literacy, particularly regarding proactive digital defense skills, information discernment in the face of "information cocoons," ethical-legal consciousness, and a profound understanding of the administrative integrity of the digital domain. To address these gaps, this paper proposes a "triad" educational framework that integrates Value Guidance, Capability Development, and Practical Empowerment. Furthermore, it advocates for a multi-stakeholder collaborative governance model involving regulatory bodies, educational institutions (with a focus on the practical strengths of vocational universities), social entities, families, and the youth themselves. This comprehensive approach aims to cultivate a new generation of "responsible netizens" capable of promoting public well-being while navigating the complexities of the digital age, thereby providing robust human capital for the construction of a safe and autonomous digital landscape.